2019
DOI: 10.7759/cureus.4775
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Porphyromonas Gingivalis Bacterium Causing Periodontal Disease on the Pathogenesis of Rheumatoid Arthritis: Systematic Review of Literature

Abstract: Periodontal pathologies are highly widespread throughout the world. Epidemiological studies have shown that as much as 1% of the population is suffering from periodontal disease. In recent years, there has been a growing number of studies linking these diseases with autoimmune diseases, especially with rheumatoid arthritis. This literature review evaluates changes in the relationship between periodontal pathologies caused by the bacterium Porphyromonas gingivalis and rheumatoid arthritis. The systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…The PPAD enzyme produced by P. gingivalis not only disturbs the balance of amino acids, but also destroys the entire body's immune system. It makes the Ag/Ab complexes imbalance, and the human body produces citrullinated antibodies against self-antigens ( Kriauciunas et al, 2019). Gabarrini et al found that PPAD can be associated with OMVs and modified by A-LPS to protect PPAD from proteolytic degradation (Gabarrini et al, 2018).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…The PPAD enzyme produced by P. gingivalis not only disturbs the balance of amino acids, but also destroys the entire body's immune system. It makes the Ag/Ab complexes imbalance, and the human body produces citrullinated antibodies against self-antigens ( Kriauciunas et al, 2019). Gabarrini et al found that PPAD can be associated with OMVs and modified by A-LPS to protect PPAD from proteolytic degradation (Gabarrini et al, 2018).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…In contrast, health-related species are at a disadvantage under this environmental condition, causing imbalances and further exacerbating inflammation, which eventually results in individual periodontitis ( Lamont et al., 2018 ). At the same time, P. gingivalis can be detected in other sites such as synovial fluid and plasma, suggesting its potential correlation with systemic diseases ( Kriauciunas et al., 2019 ). It can also interact with the host to promote gene enrichment related to Alzheimer’s disease, diabetes and cardiovascular disease, and even aggravate inflammation at the level of the central nervous system, which is conducive to the occurrence of diseases ( Carter et al., 2017 ; Dioguardi et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA sequences from Pg have been isolated from the synovial fluid and bloodstream of patients with rheumatoid arthritis (RA). Further to this, the consistently reported relationship between an oral Pg infection and RA has encouraged medical clinicians to place more emphasis on the oral health of their patients [71].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…This is difficult to reconcile with the assumed pathomechanism of the disease. Possibly, the positive effect of antibiotics observed by some authors is related to the fact that in patients with rheumatic disorders, antibodies of anaerobic microorganisms, especially periodontal bacteria, may be increased [31]. However, the approach that seems to be more appropriate is that some antibiotics, especially those that are repeatedly discussed for the treatment of rheumatic diseases, have anti-inflammatory partial effects that run independently of their anti-infective effects [32].…”
Section: Antibioticsmentioning
confidence: 99%